Pendidikan Akhlak Perspektif Ibnu Qoyyin Al-Jauziyyah dan Relevansinya dengan Pendidikan Modern - Suchi Nurul Khofifah; Afrahul Fadhilah Daulay; Sapri Sapri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the concept of moral education from the perspective of Ibn Qayyim al-Jawziyyah and analyze its relevance to modern education. The background of this research is based on the increasingly complex phenomenon of moral degradation in the era of globalization, which is characterized by the rise of deviant behavior among students, such as a lack of manners, low sense of responsibility, and a crisis of role models. Ibn Qayyim al-Jawziyyah’s educational thought is considered a potential solution because it emphasizes moral development based on the Qur’an and Sunnah through spiritual, psychological, and practical approaches. This research employed a qualitative method using a library research design to explore in depth the concept of moral education according to Ibn Qayyim al-Jawziyyah. The study applied a historical approach within the framework of a biographical study. The primary data sources were Ibn Qayyim al-Jawziyyah’s works, namely Tuhfat al-Mawlūd bi Ahkām al-Mawlūd and Madārij al-Sālikīn, while secondary data were obtained from books, journals, and other relevant literature. Data were analyzed using content analysis techniques. The findings reveal that Ibn Qayyim al-Jawziyyah’s concept of moral education includes purification of the soul (tazkiyat al-nafs), habituation of righteous deeds, exemplary role modeling, and the importance of a supportive educational environment. This concept has strong relevance to modern education, particularly in strengthening character education, developing the affective domain, and integrating spiritual values into modern educational systems to cultivate noble character.